Lesion Characteristics Of Recurrent Aphthous Stomatitis In Oral Medicine Patients: An Analysis Of Medical Record And Demographic Data - Nurfianti; Audiawati; Ahmad Ronal; Faezah Rokhani (UNIVERSITAS YARSI, 2024)
Background: Recurrent aphthous stomatitis (RAS) is an ulcerative condition that is common in the oral mucosa, especially in young women. Objectives: This study aims to analyze lesion profiles of RAS and identifying predisposing factors that play a role in its occurrence. Methods: Descriptive study was conducted from secondary data search. The sample collected from medical records of patients with a diagnosis of RAS at YARSI Dental Hospital (RSGM) during 2016-2020. Results: Data were collected from 102 patients, showing the highest prevalence in the age group of 20-29 years old (64.7%) with female majority (76.5%). The most common RAS lesions were found on the labial (35.9%) and buccal (31.3%) mucosal areas, with ulcer lesion types (87.9%) being predominant. Lesion healing duration mostly ranged from 7-14 days (94%), while the main triggering factors identified were mechanical trauma (41.9%) and stress (21%). Conclusion: Recurrent aphthous stomatitis is more common in young women with triggering factors such as mechanical trauma and stress, and requires a multifactorial treatment plan to reduce the frequency of recurrence.